Why Do We Indulge? Exploring Motivations for Binge Watching. Issue 3 (3rd July 2018) - Sung, Yoon Hi; Kang, Eun Yeon; Lee, Wei-Na
Abstract : This study explored an expanded definition and motivations for binge-watching behavior. In addition to the number of episodes, the amount of time, frequency, and engagement in binge-watched programs were considered for the binge-watching definition. Study findings revealed that over half of the respondents of this study were light binge viewers. In addition, among a total of seven motivations identified in literature, only the entertainment motivation is a significant predictor of binge watching for those with a low level of binge watching, while both passing time and entertainment were found to be significant predictors for those with a high level of binge watching.